Effect of Oxidation temperature on the thin film samarium (III) oxide growth on germanium subtrate / Gary Tan - Gary, Tan (2018)
Searching for high-κ gate oxide has been an important task in the semiconductor industry for further downscaling. In this study, pure samarium (Sm) metal was first sputtered on germanium (Ge) substrate, and then proceeded to thermal oxidation for 15 minutes at varying oxidation temperatures of 300°C, 400°C, 500°C, 600°C and 700°C. The oxidized samples were then characterized by means of X-ray diffraction spectroscopy (XRD) and Fourier transform infrared (FT-IR) spectroscopy. According to the XRD results, the intensity of Sm2O3 phase recorded the highest value at 500°C among the experimental oxidation temperatures, and the interfacial layer compound, Sm2Ge2O7 was observed to exhibit the highest peak intensity at 300°C and decreases as the oxidation temperature increases. On the other hand, the intensity of GeO2 phase was observed to increase with the oxidation temperature, and showed the highest value at 700°C. Besides, a rapid increment in the amount of GeO2 phase grown was noticed starting from 600°C, and a relatively huge quantity of GeO2 is determined at 700°C. From Debye-Scherrer equation, the crystallite size first increases from 300°C and reaches a peak at 400°C, then decreases afterwards. Besides, the crystallite size and microstrain obtained through Williamson-Hall (W-H) analysis were observed to exhibit a decreasing trend from 600°C to 700°C for GeO2 phase. The FT-IR results give information on the existence of the Sm-O and Ge-O bonds in the resulting films. By peak matching approach, Sm-O bonds were detected in 300°C, 400°C, 500°C and 600°C samples, showing the highest intensity at 500°C, while Ge-O bonds were also detected in all samples and read the highest intensity at 700°C. Both of the characterization analyses suggest that 500°C would be the optimum oxidation temperature to grow Sm2O3 on Ge substrate.